Extraction of schizophyllan from schizophyllum commune and its anticancer affect against MCF-7 cells - Hawari, Iman (Kulliyyah of Engineering, International Islamic University Malaysia, 2015)
Schizophyllum commune is a filamentous fungus which can be found worldwide except in Antarctica. This mushroom is known for its various biological and medicinal activities and have been extensively used in Japan and China. However, the Malaysian strain is yet to be studied and researched for its biological functions. S.commune secrets schizophyllan, a homopolysaccharide that consists of β-D-(1-3)-glucopyranoseunits backbone chain linked with single β-D-(1-6)-glucopyranose group every third glucose unit at the basic chain. Schizophyllan was proved in other studies to have anticancer, antiviral and antibacterial effects. Therefore, this study aims at extracting schizophyllan from Malaysian strain S.commune using Rau and hot water methods and compare them in terms of yield and duration of operation. Additionally, it aims at examining the anticancer affect of the extract against breast carcinoma cells (MCF-7). It was shown that hot water extraction method gave approximately 10% (wt/wt) higher yield (50.79%) and the duration of extraction was 5 days compared to Rau method which consumed 3 days to operate (yield= 40.8%). The extract from the hot water extraction method was used in the in vitro cytotoxicity assay (Sulforhodamine B assay) against MCF-7 breast carcinoma cells. The IC50 obtained was 290µg/mL. This value was used in the cytokinetic study to determine the effect of schizophyllan extract on the growth kinetics of MCF-7 cells. It was shown in this study that schizophyllan extract did not change the pattern and the duration of the phases in the growth profile. However, it had effect on the maximum cells attained, which was 26 x 105 cells/mL and 16 x 105 cells/mL for the untreated (control) and treated MCF-7 cells respectively. It also affected the specific growth rate (µ control= 0.071 h-1, µ treated MCF-7= 0.011 h-1). The change in the specific growth rate leaded to change in the doubling time (control td= 17.6h, treated td= 27.4 h). Moreover, schizophyllan extract reduced the number of generations (X) from 3.7 to 3.0 indicating that schizophyllan had reduced the cell population of MCF-7 after treatment.